2012
DOI: 10.1111/j.1461-9563.2011.00560.x
|View full text |Cite
|
Sign up to set email alerts
|

Attraction to monoterpenes and beetle‐produced compounds by syntopic Ips and Dendroctonus bark beetles and their predators

Abstract: 1 Bark beetles are significant mortality agents of conifers. Four beetle species, the pine engraver Ips pini, the six-spined pine engraver Ips calligraphus sub. ponderosae, the southern pine beetle Dendroctonus frontalis, and the western pine beetle Dendroctonus brevicomis, cohabitate pines in Arizona. 2 A pheromone trapping study in ponderosa forests of Arizona determined the attraction of beetles to conspecific and heterospecific pheromone components in the presence and absence of host volatiles, and tested … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 67 publications
0
19
0
Order By: Relevance
“…As with endo-brevicomin, reported behavioural responses by D. frontalis to exo-brevicomin have varied. It has alternately been shown to reduce (Vit e and Renwick, 1971), enhance (Hofstetter et al, 2008(Hofstetter et al, , 2012Pureswaran et al, 2008a), or not significantly alter (Payne et al, 1978a) responses of D. frontalis to traps baited with frontalin and host odours. As with the endo-isomer, it has not demonstrated attractive properties when presented alone or with host odours.…”
Section: Endo-brevicominmentioning
confidence: 99%
See 4 more Smart Citations
“…As with endo-brevicomin, reported behavioural responses by D. frontalis to exo-brevicomin have varied. It has alternately been shown to reduce (Vit e and Renwick, 1971), enhance (Hofstetter et al, 2008(Hofstetter et al, , 2012Pureswaran et al, 2008a), or not significantly alter (Payne et al, 1978a) responses of D. frontalis to traps baited with frontalin and host odours. As with the endo-isomer, it has not demonstrated attractive properties when presented alone or with host odours.…”
Section: Endo-brevicominmentioning
confidence: 99%
“…Little research has been done on the role of D. frontalis pheromones in mediating reproductive isolation from closely related species, although several such species may occupy the same portions of hosts (ie, exist in syntopy), utilize the same aggregation pheromone components, and be capable of pairing in the laboratory (Armendáriz-Toledano et al, 2014Davis and Hofstetter, 2009;Hofstetter et al, 2008Hofstetter et al, , 2012Lanier et al, 1988;Moser et al, 2005;Niño-Domínguez et al, 2015a;Sullivan et al, 2012). In olfactometer studies of D. frontalis and its sibling D. mesoamericanus which jointly colonize the same hosts in the Central American region, it was found that males could readily distinguish odours of conspecific and heterospecific female gallery entrances, and ipsdienol and endo-brevicomin (compounds produced by D. mesoamericanus but not D. frontalis females) were identified as the species-specific cues that mediated this discrimination (Niño-Domínguez et al, 2015a).…”
Section: Pheromones In Reproductive Isolationmentioning
confidence: 99%
See 3 more Smart Citations